Adsorption properties of tea polyphenols by hyperbranched poly (amine-ester) - Zhu Qing; Shi Yuanxu; Fan Dongmei; Yu Cuiping; Sun Zhiming; Wang Xiaochang (浙江大学学报. 农业与生命科学版, 2014)
Tea polyphenols (TPs), as one kind of effective components in tea, are composed of catechins, anthocyanins, flavonoids, etc. Catechins take up 70% 80% of TPs. The epigallocatechin gallate (EGCG) is the most abundant and important bioactivity among TPs. Various studies have demonstrated that EGCG possesses a higher efficient bioactivity compared with other components of tea polyphenols, especially in inhibiting carcinogenesis and preventing metastasis in established tumors. Therefore, it was studied widely to develop new methods or techniques to enhance the efficiency of extraction and purification of TPs (including EGCG).Now column chromatography is the main method in purification industry of TPs. However, this technique involves of organic solvents and complex operational processes, which leads to an environmental pollution and increases the additional costs virtually. The demand for an environment-friendly and cheaper technique in TPs industry is growing rapidly while more people become to pay attention to ambient bio-environment, so seeking for some new methods or new materials is of great significance. The hyperbranched poly (amine-ester)(HPAE) is a new sort of materials, having internal cellular structure and a large amount of hydroxyl terminals. HPAE has been widely used as surface modifiers, drug carriers and adsorbents for heavy metal ions on account of its high adsorption properties and complex ability. To date, there is no research on the adsorption of tea polyphenols by HPAE. The objective of this study is to investigate the characteristics of HPAE as a new environment-friendly and low-energy adsorbent for the adsorption of tea polyphenols from aqueous solutions.The adsorbent HPAE was prepared by one step method with 1-(bis (2-hydroxyethyl) amino) pentan-3-one (as a AB2 monomer) and 2-ethyl-2-(hydroxymethyl)-1, 3-propanediol (as a core molecule) in our laboratory. The kinetic experiments of adsorption were done with 10 mL HPAE (1%, w/w) and 40 mL 98% TPs solution (3.5 g/L) under the condition of 298 K and pH 7.0. The TPs contents in supernatant were determined by HPLC methods. The experiments about effects of different pH values (from 4.0 to 8.0) on adsorption also were done with similar steps with 40 mL TPs solution (1.25 g/L). Finally, the comparison of the adsorption capacity was made among HPAE and 16 kinds of traditional macroporous resins under the same condition of 298 K, pH=7.The results indicated that the adsorption of tea polyphenols by HPAE increased with time and reached equilibrium time in six hours of contact. The experimental value of the equilibrium adsorption capacity Qe (Exp) was 279.69 mg/g. The R2 values were 0.614 8, 0.997 7 and 0.744 5 for the pseudo-first-order kinetic model, pseudo-second-order kinetic model and intraparticle diffusion kinetic model, respectively. The pseudo-second-order kinetic model due to its higher R2 value and closest Qe, 2 (Cal), was considered to be the best choice to describe the adsorption behavior of tea polyphenols by HPAE, suggesting that the adsorption mechanism might be a physical adsorption process. The increase in pH from 4 to 8 resulted in the increase in the TPs adsorption capacity, indicating that pH had an obvious effect on the TPs adsorption capacity onto HPAE and adsorbed tea polyphenols could be desorbed by controlling pH value in acid medium. The maximum adsorption capacity of HPAE was 194.90 mg/g at the present experiment condition, and far greater than the adsorption capacity of macroporous resins studied widely in TPs industry, such as LSA-8, LSA-20, XDA-1, HPD600, NKA, AB-8, D3520, D4020, PVPP and PA, etc.In conclusion, the new adsorbent HPAE has excellent adsorption and desorption properties for tea polyphenols. Its adsorption capacity could achieve 194.90 mg/g, and adsorption of TPs could be desorbed easily by adjusting pH instead of using organic solvents. HPAE shows a great potential as an environment-friendly and high efficiency substitute materials for tea comprehensive processing.